A new propeller trapezius muscle flap for reconstruction of posterior trunk defects: An anatomic study and report of three cases. Issue 5 (3rd December 2018) - Meyerson, Joseph; O'Brien, Andrew; Calvin, Nicholas; Chandawarkar, Rajiv
Abstract : Background: Reconstruction of complex back defects, especially after corrective spine surgery, is a challenging problem. In these patients hardware issues predominate and flap failure has serious consequences. Certain subunits of the back pose even greater problems, specifically the central region between T9 and T12. The purpose of this article is to present a novel technique for reconstruction of such spinal defects using a newly described trapezius muscle propeller flap based on the dorsal scapular vessels. Methods: Four cadaveric trapezius muscle propeller flaps were raised to ensure appropriate rotation into central region of the posterior trunk between T9 and T12. Three patients all had similar presentations with a history of scoliosis, previous failed spinal instrumentation, prominent hardware, impending exposure, worsening kyphosis, and back pain. The patients underwent planned extension fusions from the upper thoracic to lumbar vertebrae by orthopedic surgery. All three patients lacked local reconstructive options and propeller trapezius muscle flaps were dissected. Results: All cadaveric dissections demonstrated adequate rotation of the muscle flap without tension or kinking of the vascular pedicle. For the case studies, two patients had right sided trapezius flaps utilized, one patient had injury to the right dorsal scapular vessels during dissection, thus a left sided trapezius was rotated. One patient had complications including a seroma requiring aspiration and superficial wound breakdown. All had complete healing with no postoperative shoulder dysfunction noted. Conclusion: As a result, the trapezius muscle propeller flap is found to be a novel flap that provides a simple, yet robust solution to an otherwise difficult reconstructive problem.